2012
DOI: 10.1007/s10897-012-9535-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Parental Disclosure of a 22q11.2 Deletion Syndrome Diagnosis and Implications for Clinicians

Abstract: Most children with chromosome 22q11.2 deletion syndrome (22q11DS) have an IQ in the range that may allow them to be capable of understanding a genetic diagnosis despite mild intellectual disabilities. However, there are no publications that relate to the disclosure of a 22q11DS diagnosis to the affected child, or the factors that influence parents’ disclosure to the child. A pilot study was conducted including eight semi-structured interviews with caregivers of children with 22q11DS, 10 to 17 years of age, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Indeed, qualitative accounts have shown that non-disclosure creates secrecy that negatively impacts family cohesion, causing children to feel stressed, frustrated, resentful, and anxious (Claflin & Barbarin 1991; Metcalfe et al 2008; Plumridge et al 2011). A positive disclosure experience for children occurs when children are informed about their diagnosis in a timely manner, taking cognitive development into account, with the opportunity for continued discussion (Faux et al 2012; Metcalfe et al 2011; Plumridge et al 2011). …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, qualitative accounts have shown that non-disclosure creates secrecy that negatively impacts family cohesion, causing children to feel stressed, frustrated, resentful, and anxious (Claflin & Barbarin 1991; Metcalfe et al 2008; Plumridge et al 2011). A positive disclosure experience for children occurs when children are informed about their diagnosis in a timely manner, taking cognitive development into account, with the opportunity for continued discussion (Faux et al 2012; Metcalfe et al 2011; Plumridge et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Although the communication experiences around the disorder potentially have a large impact on family functioning (Rolland, 1994), there is little research into the communication of genetic conditions, both from professionals to parents (“diagnosis”), and from parent to child (“disclosure”). The absence of advice regarding disclosure is particularly problematic when intellectual functioning is affected, as different approaches may be needed for parents to effectively communicate the diagnostic information to their children (Faux et al 2012). …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations